Experience of the menopause transition in Irish women and how it impacts motivators, facilitators, and barriers to physical activity engagement - Kelly Lee McNulty; Aoife Lane; Rosarie Kealy; Patricia Heavey (BMC Women's Health, 2024)
Abstract Background Research shows a decline in physical activity (PA) in women during the menopause transition (MT). Therefore, the purpose of this study was to explore experiences of the MT in Irish women and how it impacts motivators, facilitators, and barriers to PA engagement. Methods Twelve Irish women (age: 49 ± 4 years) who were in the MT participated in individual, online, semi-structured interviews. During each interview participants were asked about their experience of the MT and its influence on PA engagement to identify motivators, facilitators and barriers. All interviews were digitally recorded and transcribed verbatim, resulting in ≈ 72,610 words for descriptive and thematic analysis. Results The MT had a notable influence on PA engagement in Irish women. The main motivators to engage in PA throughout the MT included managing menopause symptoms, optimising future health, the opportunity for social engagement and rewards, as well as relatable role models. Many women discussed that menopause fraternities focused on community and collective experience, adapting and modifying PA, and medical supports were key factors that facilitated engagement in PA throughout this life stage. There were a multitude of barriers that women in midlife faced before they could engage in PA, such as perceived reduced capability, symptoms associated with the MT, the busyness of life and competing demands, as well as a lack of supportive environments. Conclusion The motivators, facilitators, and barriers to PA engagement throughout the MT are unique. These factors are important considerations for stakeholders when facilitating women to either continue or (re)introduce PA during this life stage.